OPTIMALISASI PENGELOLAAN TANAMAN OBAT KELUARGA (TOGA) BAGI KADER KESEHATAN DI PUSKESMAS WONOSAMODRA BOYOLALI: Optimization Of (Toga) Management at Wonosamodra Public Health Center - Reni Ariastuti; Khotimatul Khusna; Risma Sakti Pambudi; Zuliana Styarini; Nur Cahyani; Tika Dwiyanti (Pakis Journal Institute, 2023)
The government is trying and encouraging people to be independent in maintaining and maintaining health, one of which is by using family medicinal plants (TOGA). Government Regulation Number 103 of 2014 concerning Traditional Health Services in article 70 states that people can carry out health care independently and correctly by utilizing Family Medicine Parks (TOGA) and Skills. This service was carried out with the aim of increasing the knowledge and skills of Wonosamodra Boyolali health center health cadres regarding the management and use of TOGA to maintain family health. The approach method is through training and workshops to process TOGA into a health drink for families. Service participants are health cadres in the Wonosamodra Community Health Center working area, Boyolali. Service activities include providing material about TOGA and training in making health drinks from TOGA basic ingredients. The success of this service activity can be seen from the enthusiasm of the training participants in participating in the training as well as the ability/skills of the training participants in making health drink preparations, namely instant ginger powder and the health drink